ACID-SENSING ION CHANNEL 1 CONTRIBUTES TO NORMAL OLFACTORY FUNCTION - Vann, Kiara T. (Behav Brain Res, 2017)
Acid-sensing ion channels (ASICs) are cation channels activated by protons. ASIC1a, a primary ASIC subunit in the brain, was recently characterized in the olfactory bulb. The present study tested the hypothesis that ASIC1a is essential for normal olfactory function. Olfactory behavior of wild-type (WT) and ASIC1(−/−) mice was evaluated by using three standard olfactory tests: (1) the buried food test, (2) the olfactory habituation test, and (3) the olfactory preference test. In buried food test, ASIC1(−/−) mice had significantly longer latency to uncover buried food than WT mice. In olfactory habituation test, ASIC1(−/−) mice had increased sniffing time with acidic odorants. In olfactory preference test, ASIC1(−/−) mice did not exhibit normal avoidance behavior for 2, 5- dihydro-2, 4, 5-trimethylthiazoline (TMT). Consistent with ASIC1 knockout, ASIC1 inhibition by nasal administration of PcTX1 increased the latency for WT mice to uncover the buried food. Together, these findings suggest a key role for ASIC1a in normal olfactory function.